Déficits de memória induzidos por baixas doses de reserpina em ratos: possível relação com prejuízos no processamento emocional na Doença de Parkinson - Souza, Valéria Fernandes de (2008)
We have recently verified that the monoamine depleting drug reserpine at doses that do not modify motor function - impairs memory in a rodent model of aversive discrimination. In this study, the effects of reserpine (0.1-0.5 mg/kg) on the performance of rats in object recognition, spatial working memory (spontaneous alternation) and emotional memory (contextual freezing conditioning) tasks were investigated. While object recognition and spontaneous alternation behavior were not affected by reserpine treatment, contextual fear conditioning was impaired. Together with previous studies, these results suggest that mild monoamine depletion would preferentially induce deficits in tasks involved with emotional contexts. Possible relationships with cognitive and emotional processing deficits in Parkinson disease are discussed